Energetic characterization of native and exotic forest species cultivated at Amazonas - Barros, Sâmia Valéria dos Santos (2012)
The forest species Acacia mangium, Inga edulis and Tachigalia chrysophyllum were pre-selected to be used at energetic crops. In order to their characterization, tests of basic density, heating power and immediate analysis were performed. The experiment was carried out at EMBRAPA's Experimental Station, located at Iranduba/AM and was designed as randomized blocks, with three repetitions, comprising 9 plots with 25 plants each. Five trees were removed from the nine central ones of the utile area. Discs of 5 cm thick were removed from them and divided into proof bodies to evaluate basic density and other variables. Analysis of variance and Tukey test at 5% of probability were done. Acacia mangium (20.82 cm - 13.41 m) presented greater diameter and height, respectively, than the other species. The data of basic density average classified all three species as low, medium and dense-lightly density wood. The heating power observed for Acacia mangium (4430.37 kcal/kg) was statistically superior to other species. All three species presented satisfactory results at immediate analysis, being identified as suitable woods for use in burning process. Results show that the species present quality for fire wood production.